PENERAPAN MEDIA GAMBAR UNTUK MENINGKATKAN KEMAMPUAN BERBICARA PADA ANAK KELOMPOK B DI KB PUTRA BANGSA: APPLICATION OF PICTURE MEDIA TO IMPROVE SPEAKING ABILITY IN GROUP B CHILDREN AT KB PUTRA BANGSA - Efendi, Dwi Imam; Azizah, Erlin Nur (Thufuli, 2020)
This study aims to determine the extent of speaking ability through picture media in the Putra Bangsa Village Playgroup. The research approach used is Classroom Action Research with qualitative and quantitative descriptive methods. The research subjects were 24 Group B students consisting of 9 boys and 15 girls. The study was conducted in Group B at the Putra Bangsa Ngemplak Playgroup, Baureno District, Bojonegoro Regency, in the 2018/2019 Academic Year. Data were obtained through observation and documentation. The results of the study showed an increase in speaking ability through picture media in Group B at the Putra Bangsa Ngemplak Village Playgroup, Baureno District, Bojonegoro Regency, in the 2018/2019 Academic Year. This was evidenced by an increase in scores with 92.7% of children being able to speak fluently, 91.7% of children being able to speak using clear articulation, 96.9% of children being able to speak using complete sentences (S-P-O-K).